Anti-Dopamine Receptor 2 Antibody-Positive Encephalitis in Adolescent - Dai, Xuejiao; Kuang, Lilu; Feng, Li; Yi, Xiaoping; Tang, Weiting; Liao, Qiao; Long, Xiaoyan; Wang, Junling; Li, Jing; Yang, Huan; Xiao, Bo; Li, Guoliang; et al. (Frontiers in Neurology, 2020)
Autoimmune encephalitic syndromes include mutism, somnolence, movement disorder, and behavioral or psychiatric symptoms. When paired with bilateral basal ganglia lesions on magnetic resonance imaging, support the diagnosis of basal ganglia encephalitis (BGE). BGE is a rare but distinct entity of putative autoimmune aetiology, with specific basal ganglia inflammation and acute movement disorders. Previous study identified dopamine-2 receptors (D2R) antibody was positive in most BGE children, indicate D2R antibody may trigger the downstream pathological process in BGE patients. The highest levels of D2R are found in striatum, nucleus accumbens and olfactory tubercle. D2R antibody positive BGE was widely reported in children. Here, we present a 17-year-old girl with typical clinical feature of basal ganglia encephalitis benefited from immune therapy.